(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
In the field of language teaching, behaviorists assumed that the transfer of routines of the first language into the target language was responsible for the errors made by the learners while learning a foreign language. As a consequence, contrastive analysis was conducted to find out differences and similarities between languages to predict the expected difficulties of learning the target language. However, showed that language transfer could not be the only reason for committing errors, this led to questioning whether the contrastive analysis hypothesis would be valid or not. This validity of the contrastive analysis hypothesis led to the concept of ’ Interlanguage’. The theory claims that there is a system existed somewhere between the language of the mother tongue and the target one to be taught or learned by the learners. This research is designed in order to provide insights into the Libyan (Arabic-English) Interlingual and Intralingual error sources by analyzing their written essays.